2021
DOI: 10.3389/fgene.2020.596174
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Key Modules and Hub Genes of Annulus Fibrosus in Intervertebral Disc Degeneration

Abstract: Background: Intervertebral disc degeneration impairs the quality of patients lives. Even though there has been development of many therapeutic strategies, most of them remain unsatisfactory due to the limited understanding of the mechanisms that underlie the intervertebral disc degeneration.Questions/purposes: This study is meant to identify the key modules and hub genes related to the annulus fibrosus in intervertebral disc degeneration (IDD) through: (1) constructing a weighted gene co-expression network; (2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Current treatment of IDD, including conservative therapies and surgical interventions, often only alleviates the patients’ pain without preventing the progression of IDD ( Stich et al, 2020 ). Furthermore, the clinical results are suboptimal ( Wang H. et al, 2020 ). Surgical therapies are generally associated with various complications ( Smolders et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment of IDD, including conservative therapies and surgical interventions, often only alleviates the patients’ pain without preventing the progression of IDD ( Stich et al, 2020 ). Furthermore, the clinical results are suboptimal ( Wang H. et al, 2020 ). Surgical therapies are generally associated with various complications ( Smolders et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al used an integrated bioinformatics approach to generate a comprehensive overview of the gene networks associated with the AF in IVDD. This identified DSE, IL17RD, DUSP18, ROBO3, BANK1, MRC2, LGALSL, TFPI, GAP43, and HYAL1 as hub genes [ 33 ]. By constructing a PPI network, Li et al found that the MMP2 and AGE-RAGE signaling pathways as well as the estrogen signaling pathway may play important roles in the onset and development of IVDD [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…LGALSL, TFPI, GAP43, and HYAL1 as hub genes [33]. By constructing a PPI network, Li et al found that the MMP2 and AGE-RAGE signaling pathways as well as the estrogen signaling pathway may play important roles in the onset and development of IVDD [34].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the density of blood vessels and nerves is positively correlated with the degree of disc degeneration [9] . Whole-genome analysis has shown that the expression of nerve-related genes increases with the upregulation of proin ammatory cytokine and chemokine-related genes in degenerated human AF [10] . In addition, the NP, which is the largest avascular organ in the center of the disc, is uniquely isolated from the human immune system due to its anatomical structure.…”
Section: Introductionmentioning
confidence: 99%